Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment